The Japanese lover : a novel - Allende, Isabel (Atria Books, 2015)
"From internationally bestselling author Isabel Allende comes an exquisitely crafted love story and multigenerational epic that sweeps from present-day San Francisco to Poland and the United States during WWII. In 1939, as Poland falls under the shadow of the Nazis and the world goes to war, young Alma Belasco's parents send her away to live in safety with an aunt and uncle in their opulent mansion in San Francisco. There she meets Ichimei Fukuda, the son of the family's Japanese gardener, and between them a tender love blossoms. Following Pearl Harbor, the two are cruelly pulled apart when Ichimei and his family - like thousands of Japanese Americans - are declared enemies by the US government and relocated to internment camps. Throughout their lifetimes, Alma and Ichimei reunite again and again, but theirs is a love they are forever forced to hide from the world. Decades later, Alma is nearing the end of her long and eventful life. Irina Bazili, a care worker struggling to come to terms with her own troubled past, meets the older woman and her grandson, Seth, at Lark House nursing home. As Irina and Seth forge a friendship, they become intrigued by a series of mysterious gifts and letters sent to Alma, and learn about Ichimei and this extraordinary secret passion that has endured for nearly seventy years. "--